2023
DOI: 10.7150/thno.76199
|View full text |Cite
|
Sign up to set email alerts
|

Using a novel rapid alternating steering angles pulse sequence to evaluate the impact of theranostic ultrasound-mediated ultra-short pulse length on blood-brain barrier opening volume and closure, cavitation mapping, drug delivery feasibility, and safety

Abstract: Background: Focused ultrasound (FUS)-mediated blood-brain barrier (BBB) opening is a noninvasive, safe and reversible technique for targeted drug delivery to the brain. Most preclinical systems developed to perform and monitor BBB opening are comprised of a separate geometrically focused transducer and passive cavitation detector (PCD) or imaging array. This study builds upon previous work from our group developing a single imaging phased array configuration for simultaneous BBB opening and monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…This reduces, compared with long-pulse sequences [26,31,54] , the residual time for which the BBB remains disrupted, enabling rapid restoration of normal BBB functioning and, thus, neuroprotection 55 . Reduced BBB closing times following ultrasound exposure have also been reported in other mouse studies using short pulses of ultrasound [25,56] .…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…This reduces, compared with long-pulse sequences [26,31,54] , the residual time for which the BBB remains disrupted, enabling rapid restoration of normal BBB functioning and, thus, neuroprotection 55 . Reduced BBB closing times following ultrasound exposure have also been reported in other mouse studies using short pulses of ultrasound [25,56] .…”
Section: Discussionsupporting
confidence: 65%
“…Despite our ndings of a size threshold of approximately 8 to 11 nm using RaSP at 0.35 MPa, we stress that short-pulse sequences can be used to deliver larger agents using higher acoustic pressures [42] . Recently, Batts et al reported the delivery of a 4.0 MDa adeno-associated virus serotype 9 (hydrodynamic diameter: ~ 25 nm) using a different short-pulse sequence at 1.0 MPa [25] . We have also previously demonstrated the delivery of 98 nm liposomes at 0.53 MPa using the same RaSP sequence used in this study [42] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations